The effect of SARS-CoV-2 and influenza vaccination on endemic coronavirus-related mortality: A retrospective cohort study in Brazil - Char Leung; Li Su; Aleksandra Zdanowicz; Lottie Collins; Ana Cristina Simões e Silva (Human Vaccines & Immunotherapeutics)
Endemic coronaviruses (eCoVs) cause the common cold in humans, particularly affecting children, the elderly, and individuals with comorbidities, who are prone to infection-related hospitalization. While vaccination remains the most effective preventative strategy against infections, vaccines against eCoVs are not available. This study investigates the association between SARS-CoV-2 and influenza vaccination and reduced eCoV-related mortality risk. Data from Brazil’s nationwide hospital database included patients PCR-positive for one of four eCoV strains, with known admission and clinical endpoint dates, and either vaccinated against SARS-CoV-2 and/or influenza or unvaccinated. Cox regression assessed the vaccines’ effectiveness in reducing 90-day in-hospital all-cause mortality. Of 4,283,391 registered cases, 2,636 were eCoV infections. Influenza vaccination, primarily inactivated formulations, was associated with a 39% lower mortality hazard. Conversely, SARS-CoV-2 vaccination showed no significant mortality reduction. This disparity may stem from SARS-CoV-2 vaccines targeting the spike protein, which differs markedly from eCoV spike proteins, limiting cross-protection. In contrast, inactivated influenza vaccines may reduce eCoV mortality through trained innate immunity and cross-reactive cellular responses, offering broader protective effects against these viruses.